THE DEVELOPMENT of a SAFE and OPTIMIZED GENE THERAPY for HUMAN DISEASES - Alva Supit; Linda Tompodung (Universitas Negeri Medan, 2019)
Gene therapy is the therapeutic delivery of a gene or nucleic acid into a patient’s cells to cure or alleviate the symptoms of a disease that was caused by genetic malfunction, either gain- of loss-of function. Throughout the years, gene therapy has been faced with fluctuations of development before reaching its current stage. In the early stage, gene therapy was concerned to possess several problems such as toxicity, mutagenesis, and adverse immune responses which would harm the patients, instead of benefiting them. Fortunately, gene therapy has currently reached the phase where its administration can be performed in a safe, controllable manner with a good tolerability and excellent therapeutic effect. This review will recite the development of gene therapy research, highlight the vector-related safety issues, and discuss the latest updates in recent clinical trials with promising results in correcting gene defects in the cell, reducing the symptoms of the disease, as well as improving the patient’s quality of life.